EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF PEER TUTORING DAN TGT DENGAN TEKNIK TALKING CHIPS TERHADAP PRESTASI DAN MINAT BELAJAR MATEMATIKA DITINJAU DARI GAYA BELAJAR - Susanti, Sarah Wahyu; Budiyono, Budiyono; Slamet, Isnandar (Program Studi Magister Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan UNS, 2016)
Abstract: The aim of this research was to determine the effect of learning models toward the learning achievement in Mathematics and the learning interest viewed from the learning styles. The learning models compared were Cooperative Learning Model of Peer Tutoring and Teams Gamest Tournament with the talking Chips Technique. This research used the quasi experimental research method. Its population was all of the students in Grade XI of Senior High Schools of Surabaya City. The samples consisted of 223 students, and they were divided into two groups. First group consisted of 112 students who are for experimental class 1, and the other consiststed of 111 who are for experimental class 2. The instruments used were test of achievement in Mathematics learning, questionaire of learning interst and learning styles. The data was analyzed using multivariate analysis of variance. The results of the research show that: (1) the students exposed to the TGT-TC have a better learning achievement than peer tutoring; (2) the students exposed to peer tutoring have a better learning interest than TGT-TC; (3) the kinesthetic style have learning achievement as well as the auditory style, and the kinesthetic and auditory style have a better learning achievement than the visual style; (4) the kinesthetic style have learning interst as well as the visual style, and the kinesthetic and visual style have a better learning interest thanÂ the auditorial style; (5) in each learning model, either in the cooperative learning model of the peer tutoring or in TGT-TC, the students with kinesthetic style have learning achievement as well as those with auditory style, and the students with kinesthetic and auditory style have a better learning achievement than those with visual style; (6) in each learning model, either in peer tutoring or TGT-TC, the students with kinesthetic style have learning interest as well as those with visual style, and the students with kinesthetic and visual style have a better learning interst than those with auditory style; (7) in each type of learning styles, either the kinesthetic, auditory, and visual, the students have a better learning achievement in Mathematics than peer tutoring; and (8) in each type of learning styles, either the kinesthetic, auditory, and visual, the students exposed to peer tutoring have a better learning achievement in Mathematics than TGT-TC.Key words: Peer Tutoring, TGT, Talking Chips, learning styles, learning achievement, and learning interst.Â